Improved Communication Skills Assisting Cancer Patients Through Counseling Training Palliative Volunteers in Surabaya - Putra, Patria Yudha; Febria Rike Erliana; Novelita Mesah; Feytie Magda Mawey; Lia Jessica; Christopher Aditya Purba; Pemilda Dian Catur Ayu Wisnu Putri; Eden; Deviyana Soetjipto; Konginan, Agustina; Erikavitri Yulianti; Soetjipto; Marlina S. Mahajuddin (Faculty of Medicine, Universitas Airlangga, 2022)
Introduction: The prevalence of tumors/cancer in Indonesia is increasing. Many cases of cancer at an advanced stage experience severe symptoms and cause suffering that has not been handled properly. Palliative care helps a cancer survivor and his or her family to live a more comfortable life to have a better quality of life. Methods: For this reason, a team that works in an integrated manner includes both medical and non-medical personnel, including volunteers. The role of volunteers in palliative care teams varies according to need and can be involved in hospital care, or at home, expected to bridge between health care institutions and patients. Psychiatrists at Dr. Soetomo General Hospital Surabaya and their residents try to give four sessions of volunteer training to raise awareness, provide health education, or even provide some simple type of medical care and work as counselors. Results: After giving four training sessions every week, the ability of palliative teams had increased. They have the capability to communicate more effectively and efficiently, which is therapeutic, so it is necessary to provide them with counseling skills to listen to, understand, and respond positively when communicating with cancer patients and their families.